New Fixed Point Results of Generalized $g$-Quasi-Contractions in Cone $b$-Metric Spaces Over Banach Algebras (Analysis in Theory and Applications, 2017)
In this paper, we introduce the concept of generalized $g$-quasi-contractions in the setting of cone $b$-metric spaces over Banach algebras. By omitting the assumption of normality we establish common fixed point theorems for the generalized $g$-quasi-contractions with the spectral radius $r(\lambda)$ of the $g$-quasi-contractive constant vector $\lambda$ satisfying $r(\lambda) \in [0,\frac{1}{s})$ in the setting of cone $b$-metric spaces over Banach algebras, where the coefficient $s$ satisfies $s\ge 1$. The main results generalize, extend and unify several well-known comparable results in the literature.
Keywords: Cone $b$-metric spaces over Banach algebras; non-normal cones; $c$-sequences; generalized $g$-quasi-contractions; fixed point theorems.